2015
DOI: 10.1371/journal.pone.0136077
|View full text |Cite
|
Sign up to set email alerts
|

The Association between HMGA1 rs146052672 Variant and Type 2 Diabetes: A Transethnic Meta-Analysis

Abstract: The high-mobility group A1 (HMGA1) gene has been previously identified as a potential novel candidate gene for susceptibility to insulin resistance and type 2 diabetes (T2D) mellitus. For this reason, several studies have been conducted in recent years examining the association of the HMGA1 gene variant rs146052672 (also designated IVS5-13insC) with T2D. Because of non-univocal data and non-overlapping results among laboratories, we conducted the current meta-analysis with the aim to yield a more precise and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Key roles of Notch signaling also include regulation of adipocyte homeostasis and skeletal muscle homeostasis ( Bi & Kuang, 2015 ). One upstream regulator of JAG1, HMGA1 is also involved in the molecular mechanism of T2D ( Bianco et al, 2015 ). It has been reported that the expression of JAG1 is down-regulated upon HMGA1 depletion by siRNA ( Pegoraro et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Key roles of Notch signaling also include regulation of adipocyte homeostasis and skeletal muscle homeostasis ( Bi & Kuang, 2015 ). One upstream regulator of JAG1, HMGA1 is also involved in the molecular mechanism of T2D ( Bianco et al, 2015 ). It has been reported that the expression of JAG1 is down-regulated upon HMGA1 depletion by siRNA ( Pegoraro et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies from our group have demonstrated the role of HMGA1 in the transcriptional control of glucose metabolism, being a key regulator of the insulin receptor ( INSR ), insulin-like growth factor binding protein 1 ( IGFBP1 ), retinol binding-protein 4 ( RBP4 ), visfatin , and insulin ( INS ) genes ( 88 93 ), as well as an important mediator of insulin action ( 94 ). Defects in HMGA1 protein, or the association with functional HMGA1 variants, among which the most common rs139876191 variant (previously named rs146052672), cause a decrease in INSR expression and a trans-ethnic increased susceptibility to either type 2 DM ( 26 , 95 98 ) or metabolic syndrome ( 99 ). Besides its effects on glucose homeostasis, HMGA1 plays a role in adipogenesis and lipid metabolism ( 100 102 ), while the HMGA1 rs139876191 variant correlates with body mass index, and reduced HDL levels in patients with metabolic syndrome and type 2 DM ( 97 , 99 ).…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…In China, the onset age of T2DM shows a younger trend, and the morbidity has been ranked first in the world [3,4]. Substantial evidence demonstrate that T2DM can be attributed by lifestyle, environmental and genetic factors [5][6][7][8]. Although the etiology of T2DM is complex and needs further study, genetic factors have been identified to be an important cause, and an increasing number of candidate genes have been identified recent years [9,10].…”
Section: Introductionmentioning
confidence: 99%